Handbook of research on smart computing for renewable energy and agro-engineering - Kharchenko, Valeriy 1938-; Vasant, Pandian (IGI Global, 2019)
"This book examines the benefits and barriers of implementing computational models to agricultural production and energy sources as well as how these models can produce more cost-effective and sustainable solutions"--
Description based on title screen (IGI Global, viewed 10/04/2019)
Keywords: Artificial intelligence; Remote area power supply systems; Renewable energy sources / Data processing; Electricity in agriculture / Data processing